Dispute over the 1974 MoU Box between Indonesia and Australia: How MoU Legally Binding in Two Countries? - Noviana Putri, Salwa; Fazari, Ariq; Ari Widodo, Nico; Fatahillah, Faishal; Dwinugraha, Satria (Universitas Negeri Semarang, 2024)
This study aims to delineate the legal authority of Memorandum of Understanding (MoUs) within the jurisdictions of Indonesia and Australia, particularly concerning the resolution of international civil law disputes. The research employs a normative juridical approach, utilizing legal reviews and secondary data for support. The findings reveal that in civil law states, notably Indonesia, MoUs are regarded as binding agreements in accordance with the